حافظ عبدالسلام کے ترجمہ قرآن(ترجمۃ القرآن)کا فکری وفنی مطالعہ: Translation of Quran by Hafiz Abdul Salam: Artistic & Theoretical Study - Hafiz Abdul Qayyum; Dr. Sana Ullah Hussain (MEI, 2023)
Hafiz Abdul Salam’s book”Tarjama-tul_Quran“ is one of his prominent and distinct literarywork, in which he has presented the word for word translation of Arabic words/pharases and conferred idiomatically in Urdu by avoiding luxuriance of Arabic language, he maintained the attributes of translation and conscientiously distinct it from interpretation.Undoubtedly”Tarjama-tul_Quran“writtenby acknowledging all the fundamentals of Arabic linguistics, and whilte translating those Arabic terms in with the inclusion of other letters, lead change in the meaning of the work, properly addressed with reference to the context. His work aimed to overcome the difficulties and technical irregularities committed in the other available translations, for the readers so that they may understand and better comprehend the message of alimighty Allah. This paper provides the thoughtful and technical study of ”Tarjama-tul_Quran“ and significane of Hafix Abdul Salam’s work int eh field of translation of Quran.